Developing a Culture-Based Quality Management Framework for MBA and MBS Programs at Tribhuvan University, Nepal (Shaheed Smriti Journal, 2025)
PurposeThe purpose of this study is to develop a culture-based quality management framework for the Master of Business Administration (MBA) and Master of Business Studies (MBS) programs at Tribhuvan University (TU), Nepal, by identifying key quality dimensions, examining their institutional effectiveness, and integrating them into a coherent model for sustainable quality improvement. Design/methodology/approachThe study adopts a mixed-method, framework-development approach. Primary data were collected from 290 respondents comprising students, faculty members, administrative staff, and academic leaders from constituent and affiliated management colleges of TU. Quantitative data were analyzed using descriptive statistics aligned with research objectives, while qualitative insights and literature synthesis were used to construct the proposed framework.FindingsThe findings reveal that quality assurance practices in TU’s MBA and MBS programs are predominantly compliance-oriented and weakly institutionalized. Mission–vision alignment, stakeholder engagement, curriculum relevance, faculty development, student support services, and organizational culture were found to be unevenly implemented across institutions. Organizational culture emerged as a critical mediating factor influencing the effectiveness of quality management practices.Practical implicationsThe study provides a practical, context-specific framework that can guide university administrators, quality assurance units, and policymakers in embedding quality culture beyond procedural accreditation. Shaheed Smriti Journal-202529Originality/valueThis study contributes original value by shifting quality discourse in Nepalese management education from procedural assurance toward culture-embedded quality management.